Modern Aspects of Burn Injury Immunopathogenesis and Prognostic Immunobiochemical Markers (Mini-Review) - Tatyana A. Kuznetsova; Boris G. Andryukov; Natalia N. Besednova (BioTech, 2022)
Burn injuries are among the most common peacetime injuries, with mortality ranging from 2.3% to 3.6%. At the same time, 85–90% of patients with burns are people of working age and children. Burn injury leads to metabolic disorders and systemic inflammatory response, inefficient energy consumption, and other physiological changes that can lead to dysfunction of organs and systems. The most formidable complication of burn injuries is sepsis mediated by multiple organ failure, the most common cause of poor prognosis in patients and has specific differences in these injuries. The purpose of this article was to dwell in detail on the most promising immunobiochemical markers of sepsis in the format of a mini-review, based on the main aspects of the immunopathogenesis of this complication. The pathogenesis of a burn injury and any general pathological process is based on an inflammatory reaction and large-scale changes in the skin and mucous membranes. This review is devoted to the progress in understanding the main aspects of the immunopathogenesis of burn lesions and the features of post-burn immune dysfunction, manifested by disorders in the innate and adaptive immunity systems. Attention is focused on the role in the immunopathogenesis of the development of systemic and local disorders in burn injury. Characterization of primary immunobiochemical markers of burn injury (cytokines, growth factors, C-reactive protein, procalcitonin, presepsin, matrix metalloproteinases, reactive oxygen species, nitric oxide, hemostasis parameters) is presented. The problem of treating burn lesions is associated with constant monitoring of the condition of patients and regular monitoring of specific immunobiochemical markers predicting sepsis for the timely initiation of a specific therapy.